Treatment of common variable immune deficiency. (February 2013) - Resnick, Elena S; Cunningham-Rundles, Charlotte
<x xml:space="preserve">Abstract</x> Introduction: Common variable immune deficiency (CVID) is a relatively common primary immune deficiency characterized by low serum immunoglobulins and absent or poor responses to vaccines. Most patients suffer from frequent infections but about 50% of patients also have autoimmune or inflammatory conditions of uncertain pathogenesis, requiring additional therapy. Areas covered: The authors review standard therapy on immunoglobulin treatment for CVID, an approach to the treatment of infections, and the modalities currently in use for treating inflammatory complications, including lung disease, granuloma, autoimmunity, gastrointestinal disease, lymphoma and other malignancies. Expert opinion: Immunoglobulin replacement and treatment of infections are central requirements for CVID treatment. Inflammatory complications that arise may be treated with low doses of short-term corticosteroids, but other targeted therapies and/or immunomodulators may be required. As many patients do well with standard therapy, hematopoietic stem cell transplant has not been an established therapy in CVID. While preliminary experiences with allogeneic stem cell transplantation have been reported, gene therapy has not emerged as a treatment option at this time.